Родион Щедрин: начало пути / И. А. Прохорова - Прохорова Ирина Александровна (Советский композитор, 1989)
Экземпляры: (20200722) / Инвентарный номер: 19073 / Цена: / Сис.шифр: 85.313(2)6 / Авт.знак: П 84 / ББК: 85.313(2)6